TRANSFORMATION OF TRADITIONAL TO DIGITAL MARKETING A LITERATURE STUDY ON THE IMPACT OF SOCIAL MEDIA ON CONSUMER PREFERENCES - Saida Zainurossalamia ZA; Heni Rahayu Rahmawati; Asnawati (Adisam Publisher, 2025)
This research aims to explore the transformation of traditional marketing into digital marketing, with a particular focus on the impact of social media on consumer preferences. The method used is a literature study, where various relevant research and scientific articles are analyzed to understand the development and implications of this shift. Key findings show that social media has become a highly effective tool in shaping consumer preferences through social influence, personal interactions and specially curated content. Social media platforms allow companies to reach a wider audience at a lower cost, while offering higher engagement through two-way communication and immediate feedback. The impact of social media on consumer preferences has proven to be significant in building brand awareness, loyalty and purchasing decisions. Consumers are increasingly relying on reviews, recommendations, and user-generated content in their decision-making process. Implicit in these findings is the need for companies to develop digital marketing strategies that are adaptive and responsive to the dynamics of social media, including the use of data and analytics to understand consumer behavior in more depth. This research emphasizes the importance of social media integration within a digital marketing framework, as well as the potential challenges and opportunities this change presents for businesses in the digital era.